TOOLS USED IN PEDAGOGICAL TECHNOLOGIES - M.B.Aliyeva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article analyzes the main tools used in the implementation of pedagogical technologies and their role in the educational process. The importance of verbal, nonverbal, visual, audio, and natural teaching tools is scientifically discussed. The psychological characteristics of students’ perception of information are also examined. The effectiveness of active learning methods such as lectures, round-table discussions, and debates is justified. The necessity of integrating information technologies into modern education is emphasized. The comprehensive use of pedagogical tools is considered an important factor in improving the quality of education.